Taboo Words Used in Jinengdalem Village Related to Tri Hita Karana: A Descriptive Qualitative Study - Pratama, Putu Reynald Ridana; Budasi, I Gede; Juniarta, Putu Adi Krisna (STKIP AGAMA HINDU SINGARAJA, 2024)
This study aims to identify instances of taboo phrases used in relation to the three harmonious concepts of life which in Balinese called Tri Hita Karana. In Jinengdalem Village, the research was carried out. As a result, the study design used a descriptive qualitative approach. Using three informants chosen according to a predetermined set of criteria, the researcher served as the primary instrument, equipped with an interview sheet. In-depth interviews were conducted as part of the data gathering. As the primary sources data, three informants were selected during these sessions. Pitana (2010) proposed the Tri Hita Karana concept, which is comprised of three domains: Parahyangan, Pawongan, and Palemahan. This concept served as a basis for the analysis of the data-related objective. Based on the concept of Tri Hita Karana, the results of the study show that there are 43 taboo words, which are separated into three domains: 5 connected to Parahyangan, 30 related to Pawongan, and 8 related to Palemahan.. This result suggests that the Balinese taboo words are still used by the people of Jinengdalem Village as a way to preserve their cultural legacy.